A cohort study of drink‐driving motor vehicle crashes and alcohol‐related diseases - Mark Stevenson; Peter D'Alessandro; Jack Bourke; Matthew Legge; Andy H. Lee (Australian and New Zealand Journal of Public Health, 2003)
Abstract Objectives:To elicit whether drivers involved in alcohol‐related motor vehicle crashes are more likely to have future alcohol‐related hospital admissions. Method:A population‐based cohort study of 3,286 drivers involved in a motor vehicle crash between 1988 and 1992 were followed over an eight to 13‐year period. Results:The findings from the study suggest a twofold increased risk associated with an alcohol‐related motor vehicle crash and future alcohol‐related hospital admission. The average time between an alcohol‐related motor vehicle crash and future alcohol‐related hospital admission was 12 years. Men and Indigenous Australian drivers were more likely to have a future alcohol‐related hospital admission. Conclusion:It is evident from this study that drink‐driving resulting in a motor vehicle crash and hospitalisation could be considered an indicator of a less overt problem of alcohol dependency. Implications:It is important that penalties for drink‐driving go beyond merely punitive action and provide rehabilitation.